(untitled) (Research, Society and Development, 2022)
Objective: To report the learning experience about peer training for young people aged between 14 and 29 in HIV/AIDS prevention in Belém-PA. Methodology: This is a descriptive study, with a qualitative approach of the experience report type. Peer Education was a methodology used to carry out the training process for young people and adolescents. How the Viva Melhor project was developed by peers Sabendo SJ, in order to increase HIV/AIDS (VM) prevention related to HIV/AIDS prevention, was developed by peers for discussion and training of young people, in order to increase access more advanced adolescents and young people to expanded access to HIV, holding a workshop for discussion and training on HIV. on HIV/AIDS prevention methodologies, especially HIV self-testing. Results: Four meetings were held with topics related to HIV prevention. The training process was recorded for 26 Adolescents. The education took place between the pairs in a dynamic way, where interaction between facilitators and participants was possible, enabling the exchange of knowledge from experiences, in addition to being sensitized to be multipliers to become multipliers of the knowledge built in the groups. Final considerations: In view of the above, it is concluded that the final objective has been completed. In this way, peer training is understood as approximate/approximate mechanisms of HIV prevention among adolescents and young people in the COVID-19 pandemic.